Sleep and Internalizing Symptoms in Emerging Adulthood: The Role of Ethnicity and Subjective Social Status. Issue 5 (October 2018) - Kelly, Ryan J.; Bagley, Erika J.; Gordon, Jacob D.
We examined relations between objectively and subjectively assessed sleep and self-reported psychological distress from internalizing symptoms. Consistent with a health disparities perspective, ethnicity and subjective social status (SSS) were examined as moderators of these associations. Participants were 219 individuals (18–29 years old; 51% female) from diverse ethnic (55% non-Latino White, 27% Latino, and 18% other) and socioeconomic backgrounds. Individuals self-reported on their daytime sleepiness and actigraphs measured sleep duration, sleep efficiency, and variability in sleep onset time. Path models revealed that greater daytime sleepiness and variability in sleep onset time were more robustly related to distress from internalizing symptoms for Latinos and those with lower SSS. Other interactions emerged; longer sleep duration in conjunction with higher SSS related to less distress from internalizing symptoms. The results are novel and indicate that the consideration of ethnicity and socioeconomic position holds promise for better understanding sleep during emerging adulthood.